Factors of the industrial regions’ development: opportunities for modernization on an innovative basis - Soldak, M.O.; Shamileva, L.L. (Економіка промисловості, 2018)
Modernization of the economy implies the formation of an effective industrial structure that should be modernized on an innovative basis. Using the statistical models, it will be investigated in the paper which modernization factors reveal a statistically significant relationship with the gross regional product (GRP). The purpose of the article is to test three working hypotheses: not all factors of development have a statistically significant relationship with the level of regional income; the strength of this relationship differs depending on the factor; the impact of factors and the strength of relationship depend on the level of the region’s industrial development. To do this, the regions of Ukraine were divided into three groups: industrially developed regions, regions of average industrial development and underdeveloped industrial regions. The results of modeling showed that for industrially developed regions, as well as for regions of average industrial development and underdeveloped industrial regions, the factor of R&D, innovations and of the modern sector of the economy still do not play principal role in the formation of the regional income in Ukraine. In the industrially developed regions, almost the entire amount of GRP was determined by the impact of direct foreign investment and local budgets’ revenues (excluding transfers). Moreover, the impact of the former increased significantly in 2015 in comparison with 2010. A comprehensive analysis has shown that the funds of local budgets cannot be considered as an effective resource for modernizing the economy on an innovative basis. Major part of these funds is distributed on solving current social problems in the regions. Moreover, funds of local budgets are not sufficient enough to cover the expenditures, while the share of inter-budgetary transfers in the structure of local budget revenues remains rather high. As far as foreign direct investment is concerned, for now they can compensate domestic institutions’ weakness, such as access provision to skills and capital for enterprises. On the other hand, foreign investment can be considered as the factor that restrains the development and even such that causes degradation. To provide a successful modernization of the economy, the industrial regions should rely on the internal resources for innovative growth, using the advantages and positive effects of foreign direct investment.